The Incorporation of Nanoconfined Poly(ionic liquid)s with Two-Dimensional Covalent Organic Frameworks to Enhance Proton Conduction - Yonghong Wang; Xiaoxiao Liang; Ming Wang; Jiahui Wang; Yanan Gao; Fei Lu (Molecules)
Covalent organic frameworks (COFs) hold promising potential as high-temperature proton conductors due to their highly ordered nanostructures and high specific surface areas. However, due to their limited functional groups and poor membrane-engineering properties, finding practical applications for COF-based proton-conducting materials still remains challenging. Herein, we proposed a universal strategy to fabricate proton-conducting composite membranes by the incorporation of sulfonic acid-bearing COFs and zwitterionic poly(ionic liquid)s (PILs) via in situ polymerization. Zwitterionic PILs with methanesulfonate counter ions can work as the intrinsic proton sources, and the sulfonic acid groups on the COF nanochannels can act as the extrinsic proton suppliers. Benefiting from the spatial nanoconfinement of long-range ordered nanochannels and the enhanced electrostatic interactions with PILs, the COFs with high densities of sulfonic acid groups can endow the as-prepared composite membrane (PIL@TpBD(SO3H)2) with a comparable anhydrous proton conductivity of 3.20 × 10−3 S cm−1 at 90 °C, which is much higher than that of conventional Nafion (~10−5 S cm−1 at 90 °C under anhydrous condition). 1H NMR DOSY spectra reveal that both the diffusion and dissociation of protons can be drastically facilitated upon nanoconfinement, demonstrating the promising efficiency of nanochannels in proton conduction. Moreover, the obtained composite membranes possess outstanding mechanical and thermal stability, which is crucial for their practical application. This study demonstrates proton conduction elevation in nanoconfined PILs and provides a promising insight into the engineering of stable COF-based proton-conducting materials.